Melhora do equilíbrio postural em mulheres idosas com o uso de informação sensorial adicional - Leme, Gianluca Loyolla Montanari; Carvalho, Isabela Feitosa De; Scheicher, Marcos Eduardo (Universidade de São Paulo, 2017)
ABSTRACT The natural process of human aging has morphological and physiological changes, such as balance and gait, increasing the risk of falling. Some studies have investigated the use of additional sensory information to improve body balance using a soft touch on a rigid and stationary surface, which showed a significant reduction in the body oscillation. Effects of the additional sensory information were evaluated during gait on elderly women. We evaluated 30 elderly women aged 60 or older. Sensory information was added by an infrapatellar bandage. Participants performed the tests proposed by the Dynamic Gait Index (DGI), the Timed Up and Go (TUG), and the 10-Meter Walk Test (10MWT), with and without infrapatellar bandage. Data comparisons were carried out by using paired t test and Wilcoxon test with p ≤ 0.05. There was a significant difference in the TUG (without bandage: 10.13 ± 2.1, with bandage: 9.71 ± 2.1, p = 0.0007) and DGI test (without bandage: 20.65 ± 2 1; with bandage: 22.1 ± 2.1, p = 0.002). There was no significant difference in the use of 10MWT sensory addition. The results showed that the use of additional sensory information generated by the infrapatellar bandage promoted improvement of functional mobility and physical performance in elderly women.

RESUMEN El proceso natural del envejecimiento humano presenta cambios morfológicos y fisiológicos, que altera el balance postural y la marcha, aumentando así el riesgo de caídas. Hay estudios que analizaron la utilización de la información sensorial en la mejora del balance postural empleando el toque suave en una superficie rígida y estacionaria, resultando en una significativa disminución en la oscilación corporal. Se evaluó el resultado de la información sensorial adicional durante la marcha en ancianas. Participaron treinta mujeres de más de 60 años. Se realizó la información sensorial a través de vendajes infrapatelares. Las participantes hicieron las pruebas de Dynamic Gait Index (DGI), de Timed Up and Go (TUG) y de Caminata de 10 metros (PC10m), con y sin las vendajes infrapatelares. Para la comparación de los datos se emplearon la prueba t pareada y la prueba de Wilcoxon, con p≤0,05. La comparación de la TUG (sin vendajes: 10,13±2,1; con vendajes: 9,71±2,1, p=0,0007) con la DGI (sin vendajes: 20,65±2,1; con vendajes: 22,1±2,1, p=0,002) presentó diferencias significantes. En la PC10m no presentó diferencias significantes con la utilización de vendajes. Los resultados comprobaron que la utilización de la información sensorial adicional por el vendaje infrapatelar mejoró la movilidad funcional y el rendimiento físico de ancianas.

RESUMO O processo natural do envelhecimento humano apresenta alterações morfológicas e fisiológicas, como alterações de equilíbrio e da marcha, aumentando o risco de cair. Alguns estudos investigaram a utilização da informação sensorial na melhora do equilíbrio corporal utilizando o toque suave em uma superfície rígida e estacionária, verificando uma redução significativa da oscilação corporal. Avaliou-se os efeitos da informação sensorial adicional durante a marcha em mulheres idosas. Foram avaliadas 30 mulheres com 60 anos ou mais. A adição da informação sensorial foi feita por uma bandagem infrapatelar. As participantes realizaram os testes propostos pelo Dynamic Gait Index (DGI), pelo Timed Up and Go (TUG) e pelo Teste de Caminhada de 10 Metros (TC10m), com e sem a bandagem infrapatelar. As comparações dos dados foram realizadas com o teste t pareado e o teste de Wilcoxon, com p≤0,05. Houve diferença significativa na comparação do TUG (sem bandagem: 10,13±2,1; com bandagem: 9,71±2,1, p=0,0007) e no DGI (sem bandagem: 20,65±2,1; com bandagem: 22,1±2,1, p=0,002). Não houve diferença significativa no uso da bandagem no TC10m. Os resultados mostraram que o uso da informação sensorial adicional gerada pela bandagem infrapatelar promoveu melhora da mobilidade funcional e do desempenho físico em mulheres idosas.
Improvement of postural balance in elderly women with the use of additional sensory information
La mejora del equilibrio postural de ancianas con la utilización de la información sensorial adicional
Keywords: Aged; Gait; Postural Balance; Bandages; Idoso; Marcha; Equilíbrio Postural; Bandagens